2021
DOI: 10.1177/0961203321995247
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of immune thrombocytopenia under the copayment waiver policy for pediatric patients in Korea: Data from the National Health Claims Database

Abstract: The purpose of this study was to investigate the epidemiology of immune thrombocytopenia (ITP) under the copayment waiver policy for pediatric patients in Korea. The data were collected from the National Health Insurance Claims Database of Korea. ITP was identified based on the diagnostic code D69.38 from the Korean Standard Classification of Diseases. Patients between one and 18 years old, who had at least one health insurance claim for ITP as a final diagnosis, from 1 January 2016, to 31 December 2017, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The incidence of ITP varies according to factors such as age, sex, ethnicity, geographic regions of data collection, criteria for patient identification, and study design. 1,6,[22][23][24] In a recent study conducted in Korea, it was observed that the incidence of ITP was higher among children than among adults, with a peak among children under 5 years of age and a predominance among boys. 22 In our study, a similar trend in sex distribution in the age groups was identified.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of ITP varies according to factors such as age, sex, ethnicity, geographic regions of data collection, criteria for patient identification, and study design. 1,6,[22][23][24] In a recent study conducted in Korea, it was observed that the incidence of ITP was higher among children than among adults, with a peak among children under 5 years of age and a predominance among boys. 22 In our study, a similar trend in sex distribution in the age groups was identified.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of ITP in Western countries is 2–5 per 100,000 person-years [ 1 - 5 ]. In national studies using the Korea Health Insurance Research and Assessment (HIRA) database, the incidence rate of ITP for all ages is 5.3 per 100,000 person-years, while it is 13.39 and 18.1 per 100,000 person-years for children aged <18 years [ 6 - 8 ]. ITP can be an isolated primary event or secondary to other clinical conditions.…”
Section: Introductionmentioning
confidence: 99%